"Judeoconversos" and heterodox spirituality in times of Charles V - Ropero Berzosa, Alfonso (Cuadernos de Historia Moderna, 2018)
Cornered by the laws on blood purity, by virtue of which the conversos, by the mere fact of being descendants of Jews, were disqualified from holding positions of responsibility or administration in social and religious institutions. Having been the most dynamic sector, intellectually speaking, of the society of the fifteenth century, they accused this unjust discrimination as a blow difficult to fit. With the arrival of Carlos V, they dreamed that things could change, but soon they woke up to the sad reality of what they considered a “bobo emperor” in the hands of the traditionalist party. The most restless, having no place to take refuge and give rise to their high flights, retreated into themselves in search of an inner spirituality, which was their peculiar adventure in the first third of the sixteenth century. They illuminated a Christianity of inner court that fed many later mystical aspirations, orthodox and heterodox.